2002
DOI: 10.1021/jo025615o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Macrocyclic, Potential Protease Inhibitors Using a Generic Scaffold

Abstract: A generic macrocyclic peptide structure 2 was designed as a potential inhibitor of a range of proteinases, by using as a basis for the design the known structures of a series of enzyme-inhibitor complexes. The macrocyclic nature of the target 2 was chosen so as to reduce the entropic advantage in the hydrolytic enzymatic step, and thereby to inhibit the function of the enzyme. The nature of the linking group was identified as a benzoxazole by molecular modeling, so as to preserve the recognized conformation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…The propensity of the eight octapeptides to assume secondary structures correlated with their inhibitory activities. Previous studies have shown entropy-mediated gains in affinity by constraining the conformational freedom of ligands (37)(38)(39)(40)(41)(42). In the present study, spontaneous prestructuring of the peptide might reduce the entropic penalty associated with formation of a peptide/hTS complex.…”
Section: Resultsmentioning
confidence: 57%
“…The propensity of the eight octapeptides to assume secondary structures correlated with their inhibitory activities. Previous studies have shown entropy-mediated gains in affinity by constraining the conformational freedom of ligands (37)(38)(39)(40)(41)(42). In the present study, spontaneous prestructuring of the peptide might reduce the entropic penalty associated with formation of a peptide/hTS complex.…”
Section: Resultsmentioning
confidence: 57%
“…Nonetheless, this chemical approach has been used to advantage to prepare both macrocyclic peptidomimetic and non-peptidic compounds, including renin inhibitors, [23][24][25][26][27] thrombin inhibitors (7, Figure 11.1, ring closure site and reagent used for cyclization indicated), 28,29 human immunodeficiency (HIV) protease inhibitors, 30,31 b-secretase (BACE-1) inhibitors, 32 TNF-a converting enzyme (TACE) inhibitors, 33 selective MMP-8 inhibitors, 34 protease inhibitors, 35 calpain inhibitors, 36 cholecystokinin (CCK)-B antagonists, 37 subtype selective somatostatin analogues, 38 growth factor receptor-bound protein 2 (Grb) Src homology 2 (SH2) domain inhibitors, 39 histone deacetylase (HDAC) inhibitors, 40 heat shock protein 90 (Hsp90) inhibitors, 41 PDZ domain ligands, 42 multicyclic mimics of protein loop structures, 43,44 and a wide variety of structures that target the G-quadruplex (8). [45][46][47] For this latter example, it was actually simultaneous double amide bond formation that created the ring.…”
Section: Macrolactamization and Macrolactonizationmentioning
confidence: 99%
“…84 A similar strategy was employed for the synthesis of arylthioether-containing macrocycles, where intramolecular S N Ar reactions, in addition to S N 2 processes, provided the key cyclization step in the solid phase parallel synthesis of a set of peptidomimetics. 85 In a standard solution phase S N Ar process, extensive series of macrocyclic piperazinone, pyrrolidinone and imidazole farnesyltransferase (FTase) inhibitors, with 34 as a representative example ( Figure 11.4, site of ring closure indicated) were constructed, [86][87][88] from which were also identified dual inhibitors of FTase and geranylgeranyltransferase-1 (GGTase) (35). 89 Additionally, an S N Ar approach proved useful for the assembly of aminopyrimidine macrocycles (36) that possessed inhibitory activity against both CDK and vascular endothelial growth factor receptor-2 (VEGF-R2) and exhibited in vivo oral activity in a tumour xenograft model.…”
Section: Nucleophilic Aromatic Substitution (S N Ar)mentioning
confidence: 99%
“…2-Substituted benzoxazoles have also been shown to exert analgesic (Bartsch and Erker, 1991), fungicidal, insecticidal, nematocidal (Yalcin et al, 1992), potent protease inhibitory, and anticancer activities and serve as a topoisomerase I poison (Dumez et al, 2002;Kim et al, 1996).…”
Section: Introductionmentioning
confidence: 99%